Etnolingvistika po slovensko - Stanonik, Marija (ZRC SAZU, Založba ZRC, 2017)
Divided as it is, philology is constantly improving through the emergence of new interdisciplinary sciences. One among them is ethnolinguistics. It has taken particularly firm roots in Slavic studies, especially with the Russian and Polish schools. While the diachronous researches of Nikita I. Tolstoy in Svetlana Tolstaya reach as far back as Slavic mythology, the Polish school, headed by Jerzy Bartmińsky, flirts with cognitive linguistics and is more interested, through its synchronous approach, in contemporary themes. The present monograph aims to evaluate the work carried out in this field to date and to raise awareness of the new interdisciplinary direction, which may link up the ethnologies and linguistics of different directions.